Mengoptimalkan Pembelajaran Di Era Digital: Strategi Learning Organization, Kreativitas, Dan Kualitas Layanan Untuk Meningkatkan Daya Serap Materi Siswa Di Tengah Gangguan Internet - Evilia, Wida; Nurbiyanti, Siti Ayu; Utomo, Leonardo Kir; Aplakha, Anis; Zubaidah, Siti; Pujilestari, Yulita (CV. Kurnia Grup, 2026)
Digital transformation in education presents both significant opportunities and technical challenges, particularly regarding network infrastructure stability which affects students' material absorption. This Community Service (PKM) activity aims to optimize learning in the digital era through the integration of learning organization strategies, learning creativity, and education service quality improvement at Pondok Pesantren Al-Kaffah. The primary issue addressed is the low effectiveness of material absorption during internet disruptions due to over-reliance on online media. The program's implementation used educational, participatory, collaborative, and problem-solving approaches through socialization, interactive presentations, group discussions, and simulations without full internet dependency. The results showed that the application of the learning organization concept effectively built a collaborative learning culture where students actively shared knowledge and sought independent solutions. Creativity through the use of offline visual media and interactive quizzes was proven to significantly increase student engagement and learning motivation. Furthermore, responsive service quality and the provision of backup materials helped maintain student focus despite unstable network conditions. This PKM concludes that the synergy between an adaptive organization, educator creativity, and flexible services is a crucial foundation for maintaining learning quality in the digital era.